The Role of Stakeholders in Land Acquisition for the Construction of the Gatot Subroto Underpass in Medan - Purba, Nurul Narissa; Badaruddin, Badaruddin; Kusmanto, Heri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes the role of stakeholders in the land acquisition process for the construction of an underpass on Jalan Gatot Subroto Medan. The construction of this underpass infrastructure aims to reduce congestion and improve accessibility and aesthetics of the city of Medan, especially at the Manhattan Mall intersection in Medan. This research uses a qualitative descriptive method by collecting data through interviews, observation and documentation from various related parties, including the government, land owners, contractors, supervisory consultants and local communities. The research results concluded that there were 18 stakeholders divided into 4 (four) quadrants, namely: subject; key players; other supporters and followers. The resulting conclusion is in the form of a division of roles based on the interest and strength quadrants from Reed's (2009) theory. The success of land acquisition for the construction of the Gatot Subroto Medan underpass is determined by the ability of stakeholders to work together